Probing the dynamics between the substrate and the product towards glucose tolerance of Halothermothrix orenii β-glucosidase. Issue 15 (2nd September 2021) - Konar, Sukanya; Sinha, Sushant K.; Datta, Supratim; Ghorai, Pradip Kr.
Abstract: Most β-Glucosidase (B8CYA8) are prone to inhibition by glucose. Experimentally observed specific activity of B8CYA8 on 20 mM, 50 mM, and 100 mM p -nitrophenyl-β-D-glucopyranoside ( p NPGlc) substrate concentrations show surprise dependence on the presence of 0–3 M glucose at 335 K. We found that at high substrate concentration, the enzyme shows stimulation in specific activity with glucose and the glucose inhibition curve shifts toward the right with the increase in the substrate concentration. We employed atomistic molecular dynamics simulations of β-Glucosidase from Halothermothrix orenii at different glucose and p NPGlc concentrations to provide microscopic explanations to the experimentally observed non-monotonic glucose concentration dependence of the enzyme activity. Our results show that accumulation of substrate ( p NPGlc) near the B8CYA8 catalytic site residues E166 and E354 and in the active site tunnel increases up to 0.5 M glucose when the specific activity is the highest. The number of p NPGlc in the tunnel decreases drastically when glucose concentration is more than 0.5 M, and hence the specific activity decreases. Potential of mean force (PMF) calculations showed that the most favorable interaction between p NPGlc and β-Glucosidase exists at 0.5 M glucose while at deficient and high glucose concentrations, the binding energy between the substrate and β-Glucosidase is very low. These studies provide the molecular basis towards understanding inhibition and stimulation of β-Glucosidase activity in the presence of glucose and may enable the optimum use of enzymes for the efficient conversion of high biomass loading saccharification reactions. Communicated by Ramaswamy H. Sarma